(untitled) (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2023)
Context: Palliative and end-of-life care (PEOLC) aims to relieve pain, ease suffering, and preserve dignity for terminal ill patients. Worldwide, 14% of people in need of hospice palliative care receive it. Health and social care professionals must have up-to-date knowledge to provide quality PEOLC. Open educational resources (OERs) have the potential to increase and sustain knowledge. OERs are teaching, learning, or research materials available online with content licensed for retention (preservation), reuse, revision, remix, and redistribution (5Rs). The extent of OERs on PEOLC, their characteristics, and quality remain unknown. The purpose of this integrative review is therefore to identify OERs on PEOLC for health and social care professionals, describe their key characteristics, and assess their quality. Methods: A search strategy was conducted on multidisciplinary scientific journal articles databases using the keywords “open educational resources” and “palliative care.” A manual keyword search was also completed in OERs repositories, digital educational material repositories, and video sharing websites. Online resources had to be licensed according to the 5Rs criteria, contain exercises with feedback, be in English, French, or Spanish, be targeted to health and social care professionals, and cover PEOLC. Two independent authors selected, extracted, and assessed OER characteristics using the validated Revised Medical Education Translational Resources: Impact and Quality (rMETRIQ) scale. Results: Six OERs met the selection criteria and were analyzed. Five were in English and one in French. Two provided an introduction to PEOLC and the other four addressed specific topics such as medical aid in dying, tissue donation, and pediatric PEOLC. OERs scored from 5 to 14 on quality (maximum of 21).Often, OERs were released without a peer review or transparent user review process. Conclusion: Open Educational Resources (OERs) have become critical for knowledge transfer in the health and social sciences. We demonstrated that field-specific OERs can be identified and assessed. We discovered recurring gaps in the existing open OERs on PEOLC. Students, faculty, health and social care professionals, and resource developers will benefit from the resulting list of OERs.